The effectiveness of Jigsaw Method and CIRC Method on Enhancing Students' High Order Thinking Skills with Different Self-Efficacy Levels through Blended Learning - Zubaedah Wiji Lestari; Syafryadin Syafryadin (Journal of Innovation in Educational and Cultural Research, 2022)
High-order thinking skills require people not only to remember what they have learned but to analyze and evaluate the information, and later create, use, and maximize the information. The objectives of the study is  to analyze the effect of  Jigsaw and CIRC Method on enhancing students’ reading HOTS in terms of different self-efficacy levels. This study implemented mixed methods. The study was conducted at the eleventh grade of SMAN 11 Bandung. Two classes with purposive sampling were participated in this study. The instrument were reading HOTS test supported by classroom observation.  Quantitative data were analyzed by Shapiro Wilk and Levene Test, continued by Wilcoxon Test, paired t-test, one-way ANOVA, two-way ANOVA, Mann Whitney test, and Pearson Chi-Square test, whereas the qualitative data were analyzed by content and thematic analysis.   The data revealed that the implementation of the Jigsaw Method was only effective on enhancing students' reading HOTS in low self-efficacy levels and could not enhance students' reading HOTS in moderate and high self-efficacy levels. Whereas, the implementation of the CIRC Method was not effective on enhancing students' reading HOTS in low, moderate, and high self-efficacy levels